2008
DOI: 10.1111/j.1365-2850.2007.01216.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring independent nurse prescribing for mental health settings

Abstract: The purpose of this study was to explore issues relating to the implementation of independent nurse prescribing (IP) in mental health settings. Nurse prescribing in mental health has been promoted through various policy documents and has been subject to extensive research enquiry. Independent nurse prescribing is the latest form of prescriptive authority although little is known about how it can be used in mental health settings. Focus groups were used to collect qualitative data. In total, 22 nurses and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 24 publications
5
56
0
Order By: Relevance
“…Nevertheless, a number of recurring themes could be discerned, such as the views of nurses, doctors and other parties involved concerning nurse prescribing [45,47,51,53,81,94,108,109,115,121,139], prescribing behaviours of nurses [36,43,124,126,128,129,131,137], and nurse prescribing in relation to specific diseases [38,44,84,89,91-93,101,108,116,125] - most notably concerning nurse prescribing in mental health care [21,32,39,67,76,83,100,102,104-106,132,135]. Also, a number of publications focussed on the history and evolution of (nurse) prescribing of medicines, but these remained relatively limited [5,6,46,48,49,75,90,96,103,142].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, a number of recurring themes could be discerned, such as the views of nurses, doctors and other parties involved concerning nurse prescribing [45,47,51,53,81,94,108,109,115,121,139], prescribing behaviours of nurses [36,43,124,126,128,129,131,137], and nurse prescribing in relation to specific diseases [38,44,84,89,91-93,101,108,116,125] - most notably concerning nurse prescribing in mental health care [21,32,39,67,76,83,100,102,104-106,132,135]. Also, a number of publications focussed on the history and evolution of (nurse) prescribing of medicines, but these remained relatively limited [5,6,46,48,49,75,90,96,103,142].…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 presents an overview of the (expected) year of introduction of nurse prescribing in Western European and Anglo-Saxon countries. While community nurses were the first group of nurses to start prescribing in the UK in 1998, one should note that in the years thereafter two other models of nurse prescribing were introduced there: in 2002 the form now known as 'independent prescribing' was implemented [5,6,24,32,48,49,56,68,72,76,84,87,100,101,121,124,136], followed by 'supplementary prescribing' in 2003 [5,6,24,26,27,32,35,36,40,42,46,47,49,52,56,62,67-69,72,76,78,81,83,91-94,101,104,121,123,124,136,138]. Currently, nurses in the Netherlands are awaiting for the final amendments to legislation to enable them to start prescribing [5,58,117,118], and in Spain the legal regulation of nurse prescribing is in the procedural phase [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study found that nurses and psychiatrists agreed that certain psychiatric workflows can be distributed to nurses trained to manage them. Nonetheless, interviewed nurses agreed that for independent nurse prescribing, preparation and training would be essential, beyond that provided in the current curriculum (16) . Still regarding to competence in the management of the patient disease/illness status domain, study on how mental health workers respond to women who revealed sexual abuse, in the scenario of crisis service, showed that the participants recognized the impact of sexual abuse in long term manifestation of sexual trauma and psychiatric symptoms, highlighting the different responses in physical, cognitive, emotional and spiritual experienced by individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al ((2008) argues that the level of pharmacology training in preregistration MHN does not prepare the nurse for NMP status, and that without fundamental changes in preregistration NMP MHNs will continue to lack in depth knowledge of pharmacology and therefore be reluctant to prescribe. Blanchflower et al (2013) suggested there are two factors which impact on prescribing; internal, such as the confidence to prescribe; and external, including peer pressure, legislation and disagreement with other health care professionals over what should be prescribed.…”
Section: Mental Health Nurses and Non-medical Prescribing;mentioning
confidence: 99%